The Meaning of The Hajj Ritual: William R. Roff Thoughts and His Contribution to Islamic Studies in Indonesia - Muhammad Lutfi Hakim (Dialogia, 2021)
This article aims to analyze William R. Roff’s theoretical approach to Hajj and its contribution to Islamic studies in Indonesia. This contribution arose from his concern with the very few historians of religions who made functional, analytical categories for explaining religious phenomena. This paper is a literature study and uses William R. Roff’s writing, Theoretical Approaches to the Hajj, as the primary source and analyzes it using qualitative data analysis. The author found that William R. Roff explained the implementation of the pilgrimage and its meaning by elaborating on Arnold van Gennep’s theory and Victor Turner’s thesis. The pre-implementation stage of the pilgrimage means the separation contained in the ramalan ritual (extra-Islamic) to determine the best time for the pilgrims’ departure, apologies and prayers, preparation of supplies, repayment of debts, and their obligations before the pilgrimage. The stage of the hajj implementation means the transition that is contained in the peak performance of the hajj ritual. The post-implementation phase of the Hajj means togetherness in the change in attributes, understanding of the pilgrims, and their implementation in the community life where they live. William R. Roff’s theoretical contribution to the pilgrimage, the outcome of which was satisfactory to both parties, has been used as a model by scholars and researchers for studying other religious rituals in Islam. His interpretation of the hajj ritual falls into the third phase called new Islamic studies to approach.